Design matters: on the impact of compliance program design on corporate ethics - Thomas Stöber; Peter Kotzian; Barbara E. Weißenberger (Business Research, 2019)
Corporate scandals led to an increased interest in improving managers' compliance. To this end, companies implement compliance programs including codes of conduct, compliance training, and whistle-blowing as core elements. Previous research has focused on the impact of the mere existence of one or several compliance program's elements on compliance. Compliance programs differ substantially from company to company, for instance, in how training is organized and how the code looks like. This makes direct comparisons of the results challenging. Until now, it is poorly understood if and how the design of a compliance program's element affects compliance. This paper investigates firstly, whether codes per se are an effective core element of compliance programs; secondly, whether the way a code is designed (e.g., by using examples) impacts on compliance; and thirdly, whether types of compliance training as well as whistle-blowing channels make a difference in terms of compliance and whistle-blowing. We conducted a factorial survey experiment with 1005 managers from a multinational European corporation. Our findings indicate that not the mere existence of a code but its design matters for compliance. There is evidence that more specific compliance training is more effective than general training. Our study contributes to the business ethics literature by providing insights on how design elements of compliance program's elements matter. Finally, we also contribute to business practice as we draw up guidelines for those who are responsible for their compliance programs.
Keywords: M14; 650; Compliance; Compliance programs; Codes of conduct; Compliance training; Whistle-blowing; Factorial survey experiment